2003
DOI: 10.1161/01.hyp.0000087839.72582.dd
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced TGF-β1 and TGF-β Receptor-1 Expression in Vascular Smooth Muscle Cells Is Mediated by Protein Kinase C-α

Abstract: Abstract-Sclerosis and increased matrix expression in diabetes are mediated by glucose-induced transforming growth factor (TGF)-␤1 expression. The intracellular effects of high glucose occur at least in part by way of protein kinase C (PKC). We previously described a role for PKC-␣ in glucose-induced permeability. We now investigated the hypothesis that glucose-induced expression of TGF-␤1 and its receptors (TGF-␤-R1 and -R2) are mediated by activation of this PKC isoform. TGF-␤1 and TGF-␤-R expressions were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 57 publications
3
25
1
Order By: Relevance
“…TGF-␤ 1 plays a key role in the development of renal hypertrophy and accumulation of extracellular matrix in diabetic nephropathy (43). We have recently shown that high glucose leads to a PKC-␣-dependent expression of TGF-␤ 1 in vascular smooth muscle cells under in vitro conditions (11). Surprisingly, our present findings do not support a role for PKC-␣ in the regulation of TGF-␤ 1 expression in vivo.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…TGF-␤ 1 plays a key role in the development of renal hypertrophy and accumulation of extracellular matrix in diabetic nephropathy (43). We have recently shown that high glucose leads to a PKC-␣-dependent expression of TGF-␤ 1 in vascular smooth muscle cells under in vitro conditions (11). Surprisingly, our present findings do not support a role for PKC-␣ in the regulation of TGF-␤ 1 expression in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Other isoforms were less distinctly affected (10). Recently, we showed that glucose-induced activation of PKC-␣ in vitro leads to an increased expression of transforming growth factor-␤1 (TGF-␤ 1 ) (11). We tested the hypothesis that high-glucose-induced PKC-␣ activation in vivo is a mediator of functional and structural alterations in experimental diabetic nephropathy.…”
mentioning
confidence: 99%
“…Glucose and iron have been reported to induce TGF-␤ production. 49,50 Iron is important for the expression of cell-cycle and apoptosis-related genes, 51 and it may inhibit the proliferation of Burkitt lymphoma cells. 52 Iron is also required for PMA-induced expression of certain genes 53 and is necessary for protein kinase C activity.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced expressions of TGF-β 1 and VEGF stimulated by high glucose have proven to be regulated via a PKCdependent pathway [14][15][16] . A recent study showed that PKC-α lead to an increased expression of TGF-β 1 [17] , but other studies have reported that PKC-α is only involved in the regulation of VEGF and its receptor rather than TGF-β 1 under high glucose conditions [18] . Therefore, the relations of PKC-α to TGF β 1 and VEGF need further clarification.…”
Section: Introductionmentioning
confidence: 99%